Elite perceptions of poverty and inequality - Reis, Elisa Pereira; Moore, Mick
The researchers who have written this volume are clear not only that mass poverty is still the leading humanitarian crisis in developing countries, but that, if effective policies are to be put in place, the national elites who control governments and economies need to be convinced of both the reasons why reducing poverty is in their own and the national interest, and that public action can make a difference. Remarkably, in the rapidly growing literature on poverty, this volume is the first to use survey techniques to explore Third World elites' attitudes to poverty.